Organizational Support and Employee Commitment in Public Sector: A Case Study of Kabale District Local Government, Uganda. - Nassali, Joan (Kabale University, 2023)
The goal of the study was to look into how employee loyalty in Kabale District Local Government is affected by organizational support. It was guided by three specific objectives: examining the relationship between supervisor support and effective commitment; assessing how working conditions affect continuance commitment in the public sector; and determining the extent to which rewards affect normative commitment in Kabale District Local Government. Using both qualitative and quantitative data gathering and analysis techniques, the study used a descriptive survey methodology. A sample size of 321 participants was chosen for the study using straightforward random and selective sampling methods. In order to gather data for this study, questionnaires, key informant interviews, and documentary approaches were employed. It was found that employees had benefited from supervisor support for role modelling behaviour since they joined Kabale DLG, and the majority (45.8%) agreed they had been receiving task support from their supervisor at Kabale DLG, which had improved their performance in their profession. The majority of the study's findings on how working conditions affect continuance commitment revealed 19.4% of respondents were unsure, while 78.8% objected to the physical working conditions. The majority of participants in the study (67.1%) felt secure in their employment at the end. From the study findings, it was found that the majority (51.9%) of the respondents disagreed that they receive enough pay for their work at Kabale DLG.There was a significant effect of supervisory support on affective commitment since the P-value (0.00) < 0.05, hence, the alternative hypothesis was rejected and it was concluded that “there was a relationship between supervisory support and effective commitment in Kabale District Local government.” On the correlation between rewards and normative commitment, the null hypothesis was accepted and concluded that: there was a significant positive relationship existed between rewards and normative commitment (p = < 0.01, r= .530**). The district administration should address the issue of outdated staff appointments and bias in accordance with the chief administrative officer's office, where training guidelines are evaluated.